Caulobacter crescentus Adapts to Phosphate Starvation by Synthesizing Anionic Glycoglycerolipids and a Novel Glycosphingolipid - Gabriele Stankeviciute (American Society for Microbiology, 2019)
ABSTRACT Caulobacter crescentus adapts to phosphate starvation by elongating its cell body and a polar stalk structure. The stalk is an extension of the Gram-negative envelope containing inner and outer membranes as well as a peptidoglycan cell wall. Cellular elongation requires a 6- to 7-fold increase in membrane synthesis, yet phosphate limitation would preclude the incorporation of additional phospholipids. In the place of phospholipids, C. crescentus can synthesize several glycolipid species, including a novel glycosphingolipid (GSL-2). While glycosphingolipids are ubiquitous in eukaryotes, the presence of GSL-2 in C. crescentus is surprising since GSLs had previously been found only in Sphingomonas species, in which they play a role in outer membrane integrity. In this paper, we identify three proteins required for GSL-2 synthesis: CcbF catalyzes the first step in ceramide synthesis, while Sgt1 and Sgt2 sequentially glycosylate ceramides to produce GSL-2. Unlike in Sphingomonas, GSLs are nonessential in C. crescentus; however, the presence of ceramides does contribute to phage resistance and susceptibility to the cationic antimicrobial peptide polymyxin B. The identification of a novel lipid species specifically produced upon phosphate starvation suggests that bacteria may be able to synthesize a wider variety of lipids in response to stresses than previously observed. Uncovering these lipids and their functional relevance will provide greater insight into microbial physiology and environmental adaptation. IMPORTANCE Bacteria adapt to environmental changes in a variety of ways, including altering their cell shape. Caulobacter crescentus adapts to phosphate starvation by elongating its cell body and a polar stalk structure containing both inner and outer membranes. While we generally think of cellular membranes being composed largely of phospholipids, cellular elongation occurs when environmental phosphate, and therefore phospholipid synthesis, is limited. In order to adapt to these environmental constraints, C. crescentus synthesizes several glycolipid species, including a novel glycosphingolipid. This finding is significant because glycosphingolipids, while ubiquitous in eukaryotes, are extremely rare in bacteria. In this paper, we identify three proteins required for GSL-2 synthesis and demonstrate that they contribute to phage resistance. These findings suggest that bacteria may synthesize a wider variety of lipids in response to stresses than previously observed.